CURRENT STATE AND PROSPECTS OF ACCOUNTING OUTSOURCING DEVELOPMENT IN UKRAINE - SIERIKOVA, TETIANA; LAGODIIENKO, NATALIA; SIERIKOV, DENYS (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Introduction. In conditions of high competition, ensuring the viability and competitiveness of enterprises in the long run becomes possible due to companies that specialize in certain business processes. Accounting by specialists of an outsourcing company allows not only to improve the quality and reliability of reporting, but also to reduce the cost of maintaining accounting. Outsourcing allows companies to grow by reducing payroll and overhead costs and focus on core business, optimize the company’s structure and increase its competitiveness. The purpose of the research is to analyze the current state of the outsourcing services market in Ukraine, identify the main advantages and disadvantages of using alternative forms of accounting in enterprises and justify its use as a method of modern accounting. Analysis of the current state of the outsourcing services market in Ukraine allowed us to determine that as of 2020, the country ranked 42nd in the global ranking of outsourcing attractiveness (Global Services Location Index, GSLI). In addition, in 2020, more than 20 outsourcing companies were included in the ranking of the International Association IAOP "The Global Outsourcing 100". This is due to increased infrastructure costs, improved business environment and reduced costs in the category of staff availability. Identifying the main advantages and disadvantages of using alternative forms of accounting in enterprises makes it possible to argue that the most effective form of accounting in the enterprise in modern conditions is outsourcing. This is due to the involvement of highly qualified specialists in the company’s accounting. Interchangeability of outsourced accountants allows you to quickly and painlessly change the accountant if necessary and avoids the complexity and accumulation of pressing issues. It has a number of economic advantages: savings on the payroll and savings on the current costs of the enterprise associated with the organization of the work process for the accountant. The main and significant disadvantage of alternative forms of accounting is the lack of legal framework. The expediency of using accounting outsourcing is substantiated as a progressive tool that allows the company to get rid of "routine work" and focus appropriate organizational, financial and human resources on the development of its own business, new activities, or vice versa - to focus on current issues that require special attention.